Building A Corpus of Open Ancient Greek: New Ways to Learn, Teach, and Publish - Muellner, Leonard (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
Documents the history and rationale as well as the technology for the creation of an open online corpus of Ancient Greek texts, the Free First Thousand Years of Greek. Reveals the energy on a worldwide basis for building open data along with the boundless creativity around developing software tools for teaching, research, and publishing that exploit open data in ways that were impossible before.